Perlindungan Hukum bagi Konsumen atas Penggunaan Bisphenol A pada Kemasan Air Minum - Inas Audah (Jurist-Diction, 2022)
AbstractWater is a primer human needs. The majority of Indonesian people use bottled water as a source of drinking water. Some bottled water uses polycarbonate plastic which contains bisphenol-a. Bisphenol-a is a chemical whose safety is an ongoing scientific debate, where there are several studies that state the dangers of bisphenol-a mainly for fetuses, infants, and children. This research aims to discuss the form of legal protection for consumers for the use of bisphenol-a in drinking water packaging and the obligations of the government and business actors in the use of bisphenol-a in drinking water packaging.Keywords: Consumer’s Protection; Bisphenol-A; Bottled Water. AbstrakAir adalah kebutuhan hidup manusia. Masyarakat Indonesia mayoritas menggunakan air minum kemasan sebagai sumber air minumnya. Air dengan kemasan galon menggunakan bahan plastik polikarbonat yang mengandung bisphenol-a. Bisphenol-a adalah bahan kimia yang keamanannya merupakan perdebatan ilmiah yang masih berlangsung, dimana terdapat beberapa penelitian yang menyatakan bahaya bisphenol-a utamanya bagi janin, bayi, dan anak – anak. penelitian ini bertujuan untuk membahas mengenai bentuk perlindungan hukum bagi konsumen atas penggunaan bisphenol-a pada kemasan air minum serta kewajiban pemerintah dan pelaku usaha dalam penggunaan bisphenol-a pada kemasan air minum.Kata Kunci: Perlindungan Konsumen; Bisphenol-A; Air Minum Kemasan.